2003
DOI: 10.1007/s00122-003-1237-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparative genetic analysis of quantitative traits in sunflower (Helianthus annuus L.). 2. Characterisation of QTL involved in developmental and agronomic traits

Abstract: Seed weight and oil content are important properties of cultivated sunflower under complex genetic and environmental control, and associated with morphological and developmental characteristics such as plant height or flowering dates. Using a genetic map with 290 markers for a cross between two inbred sunflower lines and 2 years of observations on F3 families, QTL controlling seed weight, oil content, plant height, plant lodging, flowering dates, maturity dates and delay from flowering to maturity were detecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
26
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(30 citation statements)
references
References 18 publications
4
26
0
Order By: Relevance
“…Not all of the genes underlying detected QTLs are expected to have experienced the same selective pressures during either domestication or improvement, however. Genetic variation for flowering has been detected in crosses between elite lines (Leon et al 2000(Leon et al , 2001Bert et al 2003), and different lines may have different recent histories of selection on flowering time by farmers in different geographic regions. This scenario would increase diversity and obscure a signature of selection.…”
Section: Discussionmentioning
confidence: 99%
“…Not all of the genes underlying detected QTLs are expected to have experienced the same selective pressures during either domestication or improvement, however. Genetic variation for flowering has been detected in crosses between elite lines (Leon et al 2000(Leon et al , 2001Bert et al 2003), and different lines may have different recent histories of selection on flowering time by farmers in different geographic regions. This scenario would increase diversity and obscure a signature of selection.…”
Section: Discussionmentioning
confidence: 99%
“…In Iran, infections of the sunflower basal stem are considered a potential threat to the entire crop. Earlier studies suggested that inheritance of resistance to S. sclerotiorum is polygenic and partial resistance to S. sclerotiorum involves many genes, each of them singly makes a relatively small contribution to the overall resistance (Castano et al 1993;Bert et al 2004). Using parental lines and their recombinant inbred lines, Davar et al (2010) identified several quantitative trait loci for partial resistance to S. slerotiorum under controlled conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Darvishzadeh et al (2010) found the inbred lines F1250/03, M5-54-1, M6-862-1, two wild accessions and two lines developed by mutagenesis to be tolerant. Although tolerant genotypes were identified, full resistance was not found (Roustee et al, 2000a;Bert et al, 2004).…”
Section: Introductionmentioning
confidence: 99%